High-frequency ultrasound associated with dermoscopy in pre-operative evaluation of basal cell carcinoma - Elisa de Oliveira Barcaui; Antonio Carlos Pires Carvalho; Paulo Marcos N. Valiante; Carlos Baptista Barcaui (Sociedade Brasileira de Dermatologia, 2014)
The recent development of high-frequency ultrasound, associated with the improved sensitivity in color Doppler, enabled the identification of various skin structures and layers. In basal cell carcinoma, the 22 MHz frequency ultrasound permits the delimitation of tumor margins, while color Doppler, determines its vascularization. We present two cases in which the association of both exams allowed an in vivo analysis of the tumor's morphology, size, thickness and vascularization, thus contributing to a better pre-operative evaluation.